Effects of In Situ Remediation on Copper Distribution and Soil Aggregate Adsorption–Desorption Characteristics in Smelter-Impacted Soil - Xu, Lei; Xing, Xiangyu; Peng, Jianbiao; Ji, Mingfei (Frontiers in Environmental Science, 2022)
To evaluate the effect of in situ chemical remediation on copper (Cu) immobilisation and migration, in situ chemically remediated soils from a smelter-impacted field were partitioned into four aggregate size fractions and their Cu adsorption characteristics were investigated. The results indicate that the highest Cu concentration occurred in the < 0.053 mm size fraction, while the highest Cu mass loading was obtained in the 0.25–2 mm size fraction (39.9–42.5%). However, in situ remediation increased the Cu mass loading levels in the > 0.25 mm aggregates. A pseudo-second-order model was used to fit the adsorption process obtained in kinetic experiments, while the data from isothermal experiments were described using the Freundlich model. The fastest adsorption rate was observed in the < 0.053 mm fraction, and the adsorption capacity of the soil aggregates improved after combined in situ remediation. The amount of Cu2+ adsorbed increased with increasing pH. The < 0.053 mm fraction exhibited lower desorption compared with the other fractions at low pH values. In addition, all particle size aggregates treated with apatite and Elsholtzia splendens had the lowest desorption rates at different pH values.